2015
DOI: 10.1016/j.susc.2015.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Structure determination of the ordered 3×3R30° phase of Ni2Si and Ni2Ge surface alloys on Ni(111) via low-energy electron diffraction

Abstract: a b s t r a c tThe ð ffiffiffi 3 p  ffiffiffi 3 p ÞR30 structures of 2-D nickel silicide and nickel germanide surface alloys on Ni(111) were investigated using quantitative low-energy electron diffraction analysis. The unit cells of the determined silicide and germanide structures contain two Ni atoms and one Si or Ge atom, corresponding to the chemical compositions Ni 2 Si and Ni 2 Ge, respectively. Both the Si and Ge atoms adopt substitutional face-centered cubic hollow sites to sit on the Ni(111) substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…As for the Ni(111) surface, on the other hand, a 3 3-R30°structure with 1/3 ML Si has been reported. [25][26][27] In this case, there is no exactly coincident bulk counterpart, but the ( 210) face of orthorhombic δ-Ni 2 Si (Co 2 Si structure) has a similar atomic configuration to the 3 3-R30°structure, although the corresponding bulk structure is not completely flat but somewhat undulating. As for the surface silicide, the unit cell of the ( 210) face of δ-Ni 2 Si is −5.3% on the c-axis and +4.4% on the ¯+ a b 2 -axis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…As for the Ni(111) surface, on the other hand, a 3 3-R30°structure with 1/3 ML Si has been reported. [25][26][27] In this case, there is no exactly coincident bulk counterpart, but the ( 210) face of orthorhombic δ-Ni 2 Si (Co 2 Si structure) has a similar atomic configuration to the 3 3-R30°structure, although the corresponding bulk structure is not completely flat but somewhat undulating. As for the surface silicide, the unit cell of the ( 210) face of δ-Ni 2 Si is −5.3% on the c-axis and +4.4% on the ¯+ a b 2 -axis.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, only a few reports discussing the structure and reaction of silicidation on metal surfaces have been published. [25][26][27][28][29][30][31] It was reported that 2 × 2 and 3 3 -R30°structures are formed by exposing a Ni(111) surface to silane at high temperatures. 25) In a later study, it was found that a one-third monolayer of Si is involved in the 3 3 -R30°structure, indicating the formation of 2-D Ni 2 Si.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a later study [5], one-third monolayer of Si was found to form the √3 × √3-R30 ° structure, which indicated the formation of a two-dimensional (2D) Ni 2 Si layer. The detailed atomic structures of the 2 × 2 and √3 × √3-R30 ° structures were determined by low energy electron diffraction (LEED) [6,7]. In addition, the Ni(100) surface implanted with Si ions and subsequently annealed was studied by transmission electron microscopy (TEM) and Rutherford backscattering spectroscopy (RBS), and epitaxial Ni 3 Si was shown [8].…”
Section: Introductionmentioning
confidence: 99%
“…) symmetry with respect to the underlying Ni(111) (1 × 1) phase, and the effective formation of the surface alloy, with Sn substituting surface Ni atom. The subject was recently re-examined by Rahman et al [23], which have demonstrated that the same ordered structure can be obtained depositing silicon and germanium on-top the Ni(111) surface followed by thermal annealing at 650 K. Structural analysis revealed a XNi 2 (X=Si, Ge) stoichiometry of the surface, in agreement with XPS [13]. Interestingly, the alloyed phases are rather stable: for example the √ 3 reconstruction of SnNi 2 is still present up to temperature of about 1000K [22] (850K for Ge(Si)Ni 2 [23]).…”
Section: Accepted Manuscriptmentioning
confidence: 99%